2016
DOI: 10.18632/oncotarget.13288
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid transcription factor FOXE1 interacts with ETS factor ELK1 to co-regulate TERT

Abstract: BackgroundAlthough FOXE1 was initially recognized for its role in thyroid organogenesis, more recently a strong association has been identified between the FOXE1 locus and thyroid cancer. The role of FOXE1 in adult thyroid, and in particular regarding cancer risk, has not been well established. We hypothesised that discovering key FOXE1 transcriptional partners would in turn identify regulatory pathways relevant to its role in oncogenesis.ResultsIn a transcription factor-binding array, ELK1 was identified to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Our results are also consistent with other studies, demonstrating that FOXE1 can interact with other factors and transactivate key genes in cancer such as SNAIL (Xu et al 2015), an E-cadherin transcriptional repressor, or TERT (telomerase reverse transcriptase), which is coregulated by FOXE1 and the ETS factor ELK1 (Bullock et al 2016). Along this line, it would be interesting to search for FOXE1 interacting partners in thyroid cancer, which may reveal unique or separate signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also consistent with other studies, demonstrating that FOXE1 can interact with other factors and transactivate key genes in cancer such as SNAIL (Xu et al 2015), an E-cadherin transcriptional repressor, or TERT (telomerase reverse transcriptase), which is coregulated by FOXE1 and the ETS factor ELK1 (Bullock et al 2016). Along this line, it would be interesting to search for FOXE1 interacting partners in thyroid cancer, which may reveal unique or separate signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we identified three important transcription factors (ELK1, ETV7 and GABPA) that may significantly influence the PTC. Bullock et al 44 claimed that FOXE1 and ELK1 established a new regulatory pathway to regulate the TCs. Jacques et al 45 found that GABPA was closely associated with human thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we investigated TFs and their relationship to DEGs in these tumours, including FOXC1. One prior study found that FOXC1 is strongly associated with thyroid cancers [55]. The overexpression of YY1 in differentiated thyroid cancers has also been noted [56].…”
Section: Discussionmentioning
confidence: 92%